"The Earth Is Not Flat Anymore": Reflections on the Impact of a Rural/Urban Educational Leadership Exchange on Place-Based Instruction - Cynthia J. Norris (Educational Considerations, 2005)
In May of 2004, an educational administration doctoral cohort of ten East Tennessee K-12 teachers and administrators visited a sample of Cincinnati public schools.